Double Ureter and Duplex System: A Cadaver and Radiological Study - Prakash, -; Rajini, Thimmiah; Venkatiah, Jayanthi; Bhardwaj, Ajay Kumar; Singh, Deepak Kumar; Singh, Gajendra (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> Purpose: To study the prevalence of duplex system and double ureter in cadavers and intravenous pyelograms in Indian population. Materials and Methods: Fifty cadavers were dissected and 50 intravenous pyelograms were examined on both (right and left) sides for the presence of duplex system and double ureter. Results: One male cadaver aged 43 years showed complete double ureter and duplex system on the right side and incomplete double ureter and duplex system on the left side. Another male cadaver aged 56 years showed incomplete double ureter and duplex system only on the right side. An intravenous pyelogram of a 43-year-old man showed incomplete double ureter along with duplex system on the right side. Conclusion: Developmental anomalies of the kidney, ureter, and urinary bladder should be kept in mind and promptly detected before the manifestations of aforementioned complications increase the morbidity of the affected individuals.